An Ostracon from Tell Nimrin - Dempsey, Deirdre (Bulletin of ASOR, 1993)
During the 1989 season of the Tell Nimrin Project, an ostracon written in an Aramaic cursive script of the late fifth to early fourth century B. C. E. was excavated. It lists the names of two recipients of some commodity, perhaps wine or oil, along with the quantity of the commodity received.